Effectiveness of Trans-Theoretical Model-Based Health Education Intervention in the Promotion of Lifestyle Changes among Adults with Metabolic Syndrome: A Randomized Controlled Trial - Okubatsion Tekeste Okube PhD; Samuel T. Kimani PhD (SAGE Publishing, 2024)
Background Evidence revealed that, 60% of deaths in the underdeveloped nations are linked to adoption of unhealthy lifestyles. The Trans-theoretical Model (TTM) has been considered a useful interventional approach in smoking cessation, drug addiction and weight control. However, its effectiveness in improving changes in dietary pattern, physical activity and alcohol consumption has not been reported. Purpose The study aimed at evaluating the effectiveness of the TTM-based health education intervention in the promotion of lifestyle changes among adults with metabolic syndrome. Methods This was an experimental design where 352 participants with metabolic syndrome were allocated to intervention and control groups. The participants were randomly assigned to receive either standard CVD care or a TTM stage-based lifestyle modification intervention for 12-months. Lifestyle patterns were assessed at baseline and endpoint. The mean difference of the subtotal TTM concept scores between pre and post intervention was evaluated using paired t -test. The chi-square test of independence was used to detect between group differences in the categorical data. Results Most of the participants were in the pre-action stage of change for their dietary intake patterns and physical activity habits at the baseline assessment with no difference between the groups. The intervention group's total level of change toward adopting a healthy lifestyle was markedly ( p  < 0.001) improved than the control group at the endpoint. The mean scores for the intervention group's stage of change, self-efficacy, and pros and cons of decisional balance all improved significantly ( p  < 0.001) from the baseline. The mean scores for the control group's pros and cons of decisional balance and stage of change also considerably ( p  < 0.05) improved from baseline to the endpoint. Conclusion The TTM- based health education intervention was effective in improving the participants' lifestyles that includes diet and physical activity. Health care providers, particularly nurses should implement TTM staged-matched educational intervention for individuals who are at risk for cardiovascular diseases.